Effect of Pretreatment Methods on the Yield of Humic Acid in Oxidized Coal - Jinfeng Si; Xingming Li (Kuangchan zonghe liyong, 2023)
This is an essay in the field of mineral processing engineering. During the mining and storage process of coal resources, a large amount of oxidized coal is formed, resulting in waste of coal resources and environmental pollution. Extracting humic acid from oxidized coal can achieve the goal of high-value utilization of oxidized coal resources. In order to further improve the content and utilization efficiency of humic acid in oxidized coal, this article uses three methods: H2O2 oxidation, concentrated H2SO4 oxidation, and reverse flotation to pretreat oxidized coal samples. The influence of these methods on the content of humic acid in oxidized coal was investigated, and the changes in oxygen-containing functional groups were analyzed using Fourier transform infrared spectroscopy (FTIR). The experimental results show that both oxidation and reverse flotation can improve the utilization efficiency of humic acid. After using H2O2 oxidation, the humic acid content in coal samples increases from 21.58% to 43.62%; After oxidation with concentrated H2SO4, the content of humic acid reached 48.51%, and the extraction rate of humic acid reached 81.08%. Extracting humic acid through reverse flotation treatment can remove some minerals, and humic acid is enriched in sediment. The extraction rate of humic acid is also improved. After oxidation treatment, the extracted humic acid has an increase in oxygen-containing groups and enhanced hydrophilicity.